(untitled) (Nordic Journal of African Studies, 2011)
This paper provides alternative viewpoints on Boadi’s (1974) analysis of the basic and the derived focus marker in Akan, his position on the focus marker’s functions, and his proposal for two underlying focus-sentences in Akan. He defines na as the basic focus marker, with the senses “exclusive, emphatic, restricting” and ne as a variant derived via a morpho-phonological rule that fuses na+yε “be.” Boadi argues that it is costly in terms of rules to establish a common underlying structure for his two underlying structures. We contradict his positions with facts supported by Akan linguistics. We establish ne as the basic focus verb/copula, and na as a variant derived from ne + a ‘relativizer’ fusion. The basic focus marker, we argue, is an equational copula/verb that joins a focused-unit and a presuppositional-constituent, the aim of which is to demand, assert, or achieve definiteness. This account allows for a common underlying focus-sentence.